Protocol: A mixed-methods study to evaluate implementation and outcomes of U.S. state telemental health policy expansion during the COVID-19 pandemic. - Lucinda B Leung; Jasmeen J Santos; José J Escarce; Susan L Ettner; Claudia Der-Martirosian; Pushpa Raja; Alexander D McCourt; John Fortney; Emma E McGinty (PLoS ONE, 2024)
Background Until the COVID-19 pandemic, it had not been possible to examine the effect of rapid policy changes surrounding telemental health on patient-reported mental health care access, costs, symptoms, and functioning. Sizable variation in telemental health use by patient race-ethnicity, age, and rurality, and in its adoption across healthcare settings, underscores the need to study equitable dissemination and implementation of high-quality telemental health services in the real world. This protocol describes an explanatory sequential mixed-methods study that aims to examine the effects of state telemental health policy expansion on patient-reported mental health outcomes, as well as the policy-to-practice pathway from the perspectives of state leaders, clinicians, and staff who care for underserved patients. Methods This study uses legal mapping research methods to characterize the effective dates and specific provisions of telemental health policies (e.g., Medicaid reimbursement, private payer laws, professional licensure requirements) before and during the COVID-19 pandemic in all 50 U.S. states and Washington, D.C. Then, we will examine state factors (e.g., COVID-19 cases, broadband internet access) explaining these telemental health policies using discrete-time hazard models. The primary quantitative analysis employs a difference-in-difference approach to predict effects on outcome measures using a nationally representative survey of individuals. Using the Medical Expenditure Panel Survey, we will examine policy effects on (a) access to, use of, and expenditures related to mental health care and (b) mental health outcomes, functioning, and employment. Finally, qualitative methods will be used to obtain feedback from state leaders, administrators, clinicians, and clinic staff members on how state telemental health policy expansion influenced mental health services delivery during the pandemic, with a focus on improving safety-net care. We will use a positive deviance approach to select key partners from 6 "high" and 6 "low" telehealth expansion states for interviews and focus groups. Discussion The overall study goal is to better understand the effect of pandemic-related state policy changes around telehealth on patient-reported mental health care access, costs, symptoms, and functioning. By characterizing variations in telehealth policies and their downstream effects, this mixed-methods study aims to inform equitable dissemination, implementation, and sustainment of high-quality telemental health services.